2017
DOI: 10.1155/2017/3918214
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Laryngopharyngeal Reflux in Singers: Perceptual and Objective Findings

Abstract: This study examines the relationship between laryngopharyngeal reflux (LPR) symptoms and oropharyngeal pH levels in singers. We hypothesized that reported symptoms would correlate with objective measures of pH levels from the oropharynx, including the number and total duration of reflux episodes. Twenty professional/semiprofessional singers completed the Reflux Symptom Index (RSI) and underwent oropharyngeal pH monitoring. Mild, moderate, or severe pH exposure was recorded during oropharyngeal pH monitoring. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Using only RSI or RFS values for the diagnosis of LPR might lead us to false-positive diagnoses. 49,52,[54][55][56] In the our sample 26.8% of the clinical group met pH monitoring diagnoses criteria and similar prevalence, detected with the same gold standard, was reported in recent contemporary scientific research from the Asian, 57,58 Europe 59 and Italy. [60][61][62] Although the threshold found with the original version is similar to the first validation work (Belafsky: 2002) the scores from RSI Binary version had better known-groups criterion validity, with prevalence values approaching the gold standard (26.8%), we would recommend this approach in future applications.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using only RSI or RFS values for the diagnosis of LPR might lead us to false-positive diagnoses. 49,52,[54][55][56] In the our sample 26.8% of the clinical group met pH monitoring diagnoses criteria and similar prevalence, detected with the same gold standard, was reported in recent contemporary scientific research from the Asian, 57,58 Europe 59 and Italy. [60][61][62] Although the threshold found with the original version is similar to the first validation work (Belafsky: 2002) the scores from RSI Binary version had better known-groups criterion validity, with prevalence values approaching the gold standard (26.8%), we would recommend this approach in future applications.…”
Section: Discussionsupporting
confidence: 81%
“…Using only RSI or RFS values for the diagnosis of LPR might lead us to false-positive diagnoses. 49,52,54-56…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of substances such as tobacco, caffeine, alcohol, and high-fat foods also favors the return of gastric contents to the glottic level, causing vocal irritation. 9 20 33 The study by Lloyd et al 34 investigated the relationship between GER symptoms and oropharyngeal pH levels in professional and semiprofessional singers, and found that mild GER was present in 95% of the participants by objective evaluation, although only 75% of the participants had signs of self-reported GER using subjective evaluation. The same occurred in another study, 13 in which among laryngeal alterations, GER was the prevalent pathology in popular singers, with a slight predominance in women 13 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lately, reflux has been increasingly associated with voice disorders among singers, whether it is related to macroscopic and microscopic changes in the mucosa of the vocal folds [6,7] or to the singers' enhanced sensitivity to it [8].…”
Section: Introduction 1singing and Riskmentioning
confidence: 99%